2021
DOI: 10.31674/mjn.2021.v13i02.004
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitude Toward Breast Self-Examination Among Young Adult Nursing Students in a Public University in Malaysia

Abstract: This study aims to identify the knowledge and attitude towards breast self-examination among undergraduate nursing students in the public university at Peninsular Malaysia. The method used in the study is a cross-sectional descriptive study that was conducted among 188 undergraduate students studied in a public university at Peninsular Malaysia. The level of knowledge and attitude of breast self-examination (BSE) measured using self-administered questionnaires. All data were analyzed using SPSS Statistics 23.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 9 publications
(18 reference statements)
3
1
0
Order By: Relevance
“…Similar with Nimir et al (2014); Ibnawadh et al (2017) where their study has discovered that nursing students had good overall knowledge towards BSE (Nimir et al, 2014;Ibnawadh et al, 2017). The researcher also believed the higher the knowledge that the young person has, the more they intend to explore the benefit of breast self-examination as early breast cancer screening (Khalip et al, 2021) Apparently, our study showed practicing on BSE does show a negative impact on attitude (R= -0.131). Wasting time, against cultural belief and not necessary for them to perform BSE were among the top excuses given by the respondents (Okolie, 2012;Haruna et al, 2017).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Similar with Nimir et al (2014); Ibnawadh et al (2017) where their study has discovered that nursing students had good overall knowledge towards BSE (Nimir et al, 2014;Ibnawadh et al, 2017). The researcher also believed the higher the knowledge that the young person has, the more they intend to explore the benefit of breast self-examination as early breast cancer screening (Khalip et al, 2021) Apparently, our study showed practicing on BSE does show a negative impact on attitude (R= -0.131). Wasting time, against cultural belief and not necessary for them to perform BSE were among the top excuses given by the respondents (Okolie, 2012;Haruna et al, 2017).…”
Section: Discussionsupporting
confidence: 86%
“…As summary, this study has concluded that education level and marital status were the only factors that contribute towards respondents' knowledge and practice. This study has revealed a significant outcome which Khalip et al (2021) in her study has mentioned that knowledge on BSE has significant relationship with educational level, which parallel with current study (p-value<0.05). Similar with Nimir et al (2014); Ibnawadh et al (2017) where their study has discovered that nursing students had good overall knowledge towards BSE (Nimir et al, 2014;Ibnawadh et al, 2017).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Similar ndings were found in another study that was conducted at a public university in Malaysia which revealed that (79.3%) of the participating nursing students had a strong understanding of breast cancer in general, (86.7%) were familiar with breast self-examination, and (33%) had undergone BSE 4 .…”
Section: Discussionsupporting
confidence: 84%
“…In this study, more than half of the respondents (72.1%) had adequate knowledge of BSE and this finding is the same as a study by Khalip et al (2021) where most respondents said they'd heard of BSE when asked about their knowledge of BSE as a whole. This finding is similar to the current findings that were consistent with a study conducted in Ethiopia, which found that the overall knowledge of female undergraduate students about BSE was adequate knowledge (Mekonnen & Asefa, 2019).…”
Section: Knowledge Of Breast Self-examinationsupporting
confidence: 85%